EDUKASI PENGENALAN DAMPAK PSIKOLOGI DARI CYBER BULLYING DIMEDIA SOSIAL BAGI SISWA - Purba, Budiman; Amin, Afriadi; Manullang, Helentina Mariance (MAJU : Indonesian Journal of Community Empowerment, 2025)
Cyberbullying is a form of bullying that occurs in the digital world through social media, which has serious psychological and physical impacts on victims, such as depression, anxiety, sleep disorders, and decreased motivation to study. Teenagers, as active users of social media, are vulnerable to this type of bullying, so anti-bullying education on social media is very important to increase awareness, empathy, and responsibility in online interactions. The community service program at MAPN 4 Medan employs interactive socialization methods, provides educational modules, and establishes peer support groups to prevent and address cyberbullying. Evaluations indicate improved understanding among students and teachers regarding the various forms and impacts of cyberbullying, as well as increased awareness of the need for proactive action in prevention. Teacher involvement and school environment support are key factors in the program's success. With ongoing education and social support, it is hoped that a safe, comfortable, and mentally healthy school environment will be created for students in the digital age